High-temperature-resistant and high-salt-resistant nano imbibition agent as well as preparation method and application thereof
Through the synergistic effect of the aminated mesoporous silica nanoparticles with nanocellulose composite carriers and other components, the performance unstable and rock adsorption problems of nano-permeable agents in high-temperature and high-salt reservoir environments are solved, and efficient crude oil recovery and equipment protection are achieved.
Patent Information
- Application Number
- CN202510877503.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-07-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing nano-permeable agents have unstable performance in high-temperature and high-salt reservoir environments, which are prone to adsorbing rocks and have poor environmental adaptability, making it difficult to effectively improve crude oil recovery.
Aminating modified mesoporous silica nanoparticles are used to form a composite carrier with nanocellulose, and combined with rhamnolipid, anionic surfactant, citrate modified sodium zirconium phosphate and polyethylene glycol-b-polycaprolactone, to form a high-temperature and high-salt nanopermeable agent. Through electrostatic action and synergistic action, the interfacial activity is improved, salting out is inhibited, and the sustained release and anti-adsorption of the active components are achieved.
It significantly improves crude oil recovery rate, reduces injection pressure and dosage, prevents reservoir blockage, and extends the life of the oil well. It is suitable for high-temperature and high-salt oil reservoirs.
Smart Images

Figure CN120383926A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oil extraction, and in particular, to a high-temperature and high-salt resistant nano imbibition agent and its preparation method and application. Background Art
[0002] In the field of oil extraction, with the gradual depletion of easily exploitable oil reservoirs, the development of unconventional oil reservoirs such as low-permeability, tight oil reservoirs, and shale oil reservoirs has become increasingly important. These reservoirs are characterized by low permeability, high viscosity of crude oil, and high capillary resistance. Traditional oil production methods often have difficulty in effectively improving the oil recovery rate (EOR). In recent years, the development of nanotechnology has provided a new approach to improving the oil recovery rate. Among them, nano imbibition agents, as a new type of oilfield chemical agent, have shown great potential in improving the fluidity of crude oil and enhancing the capillary oil displacement efficiency due to their unique nano effects and excellent interfacial properties.
[0003] At present, existing nano imbibition agent products have improved the oil recovery rate to a certain extent, but there are still many problems to be solved. First, in high-temperature and high-salt oil reservoir environments, the performance of traditional surfactants and some nano imbibition agents will decline significantly. When the formation temperature exceeds 120 °C and the salinity is as high as 200,000 ppm, conventional surfactants are prone to phenomena such as salting out and high-temperature degradation, resulting in a rapid decrease in interfacial activity and difficulty in effectively reducing the oil-water interfacial tension, thus limiting their application under harsh reservoir conditions. Second, the problem of the interaction between nano imbibition agents and the rock surface is also relatively prominent. Some nano imbibition agents are prone to irreversible adsorption in rock pores, causing loss of effective dosage and may also change the wettability of the rock, affecting subsequent production operations.
[0004] Therefore, there is an urgent need for a nano imbibition agent to solve the problems in the prior art. Summary of the Invention
[0005] The main object of the present invention is to provide a high-temperature and high-salt resistant nano imbibition agent and its preparation method and application, so as to at least solve the problems in the prior art that the existing nano imbibition agents have unstable performance, are prone to adsorb on rocks, and have poor environmental adaptability in high-temperature and high-salt oil reservoir environments.
[0006] To achieve the above object, the present invention provides a high-temperature and high-salt resistant nano imbibition agent, which, by weight percentage, includes: 15 - 25% modified mesoporous silica nanoparticles, 3 - 8% nanocellulose, 25 - 35% rhamnolipid, 8 - 12% anionic surfactant, 5 - 8% modified sodium zirconium phosphate, 8 - 12% polyethylene glycol-b-polycaprolactone, and 1 - 5% mercapto-carboxy imidazoline derivative; Among them, the modified mesoporous silica nanoparticles are amino-functionalized modified mesoporous silica nanoparticles; the modified sodium zirconium phosphate is citrate-modified sodium zirconium phosphate.
[0007] Optionally, the anionic surfactant is sodium dodecylbenzenesulfonate or petroleum sulfonate.
[0008] Optionally, the modified mesoporous silica nanoparticles have a particle size of 5 to 10 nm before modification and a specific surface area of ≥1000 m 2 / g.
[0009] Optionally, the mercapto-carboxyimidazoline derivative is one of mercapto-carboxyimidazoline quaternary ammonium salt, mercapto-carboxyimidazoline amide and mercapto-carboxyimidazoline sulfide.
[0010] Optionally, the modified mesoporous silica nanoparticles are modified by amino modification using 3-aminopropyltriethoxysilane.
[0011] The present invention also provides a method for preparing a high-temperature, high-salt resistant nano-scenting agent, which is applied to the high-temperature, high-salt resistant nano-scenting agent of the present invention, comprising the following steps: Step 1: mixing nanocellulose and amino-modified mesoporous silica in deionized water, ultrasonically dispersing the mixture, and then spray drying the mixture; Step 2: adding rhamnolipid and anionic surfactant to a buffer solution with a pH of 7 and stirring until dissolved, then adding the product obtained in step 1, stirring at 50-60° C. for 2-3 hours, performing ultrasonic dispersion, and then drying; Step 3, adding the product obtained in step 2 to deionized water dissolved with citrate-modified sodium zirconium phosphate, stirring at 50-60° C. for 1-2 hours, and performing solid-liquid separation to obtain a solid product; Step 4: adding polyethylene glycol-b-polycaprolactone, the mercapto-carboxyimidazoline derivative and the solid product obtained in step 3 into anhydrous ethanol and stirring and mixing to obtain a nano-permeating agent.
[0012] Optionally, in step 1, the preparation process of the amino-modified mesoporous silica nanoparticles includes: Mesoporous silica nanoparticles were dispersed in anhydrous toluene, 3-aminopropyltriethoxysilane was added, and the mixture was refluxed at 60-80°C for 4-6 hours under nitrogen protection.
[0013] Optionally, in step 1, the spray drying process includes: the inlet temperature is initially set to 140°C, and after running for 10-15 minutes, it begins to be gradually lowered by 2-3°C each time, and gradually lowered to 130°C. The whole process lasts for 45-60 minutes.
[0014] Optionally, the parameters of the ultrasonic treatment in step 2 include: frequency 40-60 kHz, duration 30-50 min.
[0015] The present invention also provides an application of the high-temperature and high-salt resistant nano-sorbent in petroleum production.
[0016] The technical solution of the present invention is a high-temperature and high-salt resistant nano-infiltrator and its preparation method and application, which comprises, by weight percentage: 15-25% modified mesoporous silica nanoparticles, 3-8% nanocellulose, 25-35% rhamnolipid, 8-12% anionic surfactant and 5-8% modified sodium zirconium phosphate, 8-12% polyethylene glycol-b-polycaprolactone and 1-5% mercapto-carboxy imidazoline derivative; wherein the modified mesoporous silica nanoparticles are amino-modified mesoporous silica nanoparticles; The modified sodium zirconium phosphate is citrate-modified sodium zirconium phosphate. The composite carrier formed by the amino-modified mesoporous silica nanoparticles and nanocellulose has both high mechanical strength and uniform dispersibility. The synergistic effect of rhamnolipids and anionic surfactants reduces the oil-water interfacial tension, significantly improving the efficiency of crude oil stripping. The citrate-modified sodium zirconium phosphate significantly improves the system's salt resistance and effectively inhibits salting out. PEG-b-PCL achieves efficient sustained release of the active component, reducing adsorption losses and extending the effective duration of action. Therefore, in high-temperature, high-salt oil reservoir environments, this nano-imbibition agent can significantly increase oil recovery and reduce injection pressure and dosage. It also exhibits good adsorption resistance, preventing reservoir clogging. Furthermore, its low-toxic corrosion-inhibiting components protect equipment and extend the life of the well. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings, which constitute part of this application, are intended to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are intended to explain the present invention and do not constitute an undue limitation of the present invention. In the accompanying drawings:
[0018] Figure 1 This is a flow chart of a method for preparing a high-temperature resistant and high-salt nano-infiltrator according to an embodiment of the present invention. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features of the embodiments in this application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0020] The present application provides a high-temperature and high-salt resistant nano-infiltration agent, which comprises, by weight percentage: 15-25% modified mesoporous silica nanoparticles, 3-8% nanocellulose, 25-35% rhamnolipid, 8-12% anionic surfactant and 5-8% modified sodium zirconium phosphate, 8-12% polyethylene glycol-b-polycaprolactone and 1-5% mercapto-carboxy imidazoline derivative; Wherein, the modified mesoporous silica nanoparticles are amino-modified mesoporous silica nanoparticles; and the modified sodium zirconium phosphate is citrate-modified sodium zirconium phosphate.
[0021] Specifically, the main components for preparing the nano-permeating agent include modified mesoporous silica nanoparticles, nanocellulose, rhamnolipids, anionic surfactants and modified sodium zirconium phosphate, polyethylene glycol-block-poly-ε-caprolactone copolymer and thiol-carboxy imidazoline derivatives, and the rest are solvents. Aminated modified mesoporous silica nanoparticles are used as the core carrier, and the surface activity and adsorption properties of the carrier are significantly improved by introducing amino functional groups. The presence of amino groups enables it to form electrostatic interactions with anionic surfactants, thereby stably loading active components. At the same time, the amino modification enhances the interfacial bonding force between the carrier and nanocellulose, forming a composite structure with higher mechanical strength, ensuring that it maintains integrity during high-pressure injection. This carrier not only provides high dispersibility, but also provides a stable platform for the loading of other functional components, effectively preventing the loss of active ingredients and improving the overall stability of the nano-permeating agent. Nanocellulose is a bio-based reinforcing material. Its abundant carboxyl functional groups form a strong interaction with amino-modified mesoporous silica nanoparticles, enhancing the mechanical strength of the composite carrier. This allows the nano-infiltrant to maintain structural stability under high-temperature and high-pressure conditions, preventing particle breakage and the resulting decrease in injectability. Furthermore, nanocellulose improves the dispersion and stability of the carrier, preventing particle aggregation or sedimentation in complex reservoir environments, ensuring uniform distribution and efficient performance within the reservoir.
[0022] Rhamnolipids are natural amphoteric biosurfactants with excellent interfacial activity and biodegradability. As primary surfactants, they can significantly reduce oil-water interfacial tension, promote crude oil exfoliation from rock pores, and improve microscopic oil recovery efficiency. The spontaneous adsorption ability of rhamnolipids enables them to form stable, ultra-low tension films at the oil-water interface, thereby enhancing oil recovery. Anionic surfactants are negatively charged, and because reservoir rock surfaces are often negatively charged, the electrostatic repulsion between the two reduces adsorption on the rock surface, reducing losses and improving oil recovery efficiency. The hydrophobic chains of the molecules can wrap around crude oil to form a stable emulsion, preventing oil droplet aggregation. Furthermore, in high-salt environments, electrostatic shielding reduces competitive adsorption between cations and rhamnolipids, preventing salting-out and precipitation that could deactivate the system. Compounding with rhamnolipids to form mixed micelles reduces interfacial tension and critical micelle concentration, improving system stability and oil recovery efficiency. It also prevents adsorption clogging and low-temperature emulsification failure that can be caused by cationic surfactants, thereby increasing oil recovery.
[0023] Citrate modified sodium zirconium phosphate enhances its thermal stability and salt resistance by intercalating citrate ions between layers. In high temperature and high salt environments, this component can effectively inhibit the release of high-valent cations (such as Ca 2+ Mg 2+)’s salting-out effect on the surfactant maintains the stability of the active sites, thereby ensuring the high efficiency of the nano-permeant in high temperature and high salt environments.
[0024] The molecular structure of polyethylene glycol-b-polycaprolactone (PEG-b-PCL) consists of a hydrophilic polyethylene glycol (PEG) segment and a hydrophobic polycaprolactone (PCL) segment. The PEG segment forms a hydration layer on the rock surface, preventing adsorption of nano-sorbent particles, reducing adsorption losses, and ensuring efficient delivery of active components within the reservoir. The PCL segment exhibits controlled hydrolysis, gradually releasing active components over a period of time, extending its shelf life. This enhances the sorbent's anti-adsorption capacity and long-lasting effectiveness. A thiol-carboxy imidazoline derivative is a highly effective corrosion inhibitor. Its thiol (-SH) group forms a self-assembled monolayer on metal surfaces, effectively blocking corrosive media and reducing the corrosion rate of metal equipment. The carboxyl group also enhances its water solubility, preventing deposition and clogging. This corrosion inhibitor has extremely low toxicity and protects oil well tubing and surface equipment from corrosion, extending service life and reducing maintenance costs. Its versatility allows it to enhance oil recovery while ensuring safe equipment operation.
[0025] The nano-scenting agent in this application, the composite carrier formed by amino-modified mesoporous silica nanoparticles and nanocellulose, has both high mechanical strength and uniform dispersibility. The synergistic effect of rhamnolipid and anionic surfactant reduces the oil-water interfacial tension, significantly improving the crude oil stripping efficiency; while the citrate-modified sodium zirconium phosphate greatly improves the salt resistance of the system and effectively inhibits the salting-out effect; PEG-b-PCL achieves efficient sustained release of active components, reduces adsorption losses and prolongs the effective action time. Therefore, in the high-temperature and high-salt oil reservoir environment, the nano-scenting agent can significantly improve the crude oil recovery rate, reduce the injection pressure and dosage, and at the same time has good anti-adsorption properties to prevent reservoir blockage; in addition, its low-toxic corrosion inhibition components protect equipment and extend the life of the oil well.
[0026] In one possible embodiment, the anionic surfactant is sodium dodecylbenzenesulfonate or petroleum sulfonate.
[0027] Specifically, sodium dodecylbenzene sulfonate and petroleum sulfonate both have excellent interfacial activity, which can quickly reduce the oil-water interfacial tension to below 0.1 mN / m, significantly enhancing the stripping and flowability of crude oil. Secondly, sodium dodecylbenzene sulfonate and petroleum sulfonate can form efficient mixed micelle systems with rhamnolipids, which can significantly reduce the critical micelle concentration (CMC), reduce the amount of surfactant used and improve oil recovery efficiency. In addition, sodium dodecylbenzene sulfonate and petroleum sulfonate both have good salt resistance and can effectively reduce the oil-water interfacial tension to below 0.1 mN / m. + ) conditions, it can still function stably, avoiding performance degradation caused by cation competitive adsorption. Moreover, it has a wide source and low cost.
[0028] In one possible embodiment, the modified mesoporous silica nanoparticles have a particle size of 5 to 10 nm before modification and a specific surface area of ≥1000 m 2 / g.
[0029] Specifically, the tiny size of 5-10 nm enables it to penetrate deep into the micropores of the reservoir (<100 nm), significantly improving the microscopic oil recovery efficiency; the specific surface area ≥1000 m² / g provides sufficient active sites, enabling efficient loading of components such as anionic surfactants and rhamnolipids, thereby enhancing interfacial activity.
[0030] In a possible embodiment, the mercapto-carboxyimidazoline derivative is one of a mercapto-carboxyimidazoline quaternary ammonium salt, a mercapto-carboxyimidazoline amide, and a mercapto-carboxyimidazoline sulfide.
[0031] Specifically, mercapto-carboxyimidazoline quaternary ammonium salts, mercapto-carboxyimidazoline amides, and mercapto-carboxyimidazoline thioethers contain both thiol (-SH) and carboxyl (-COOH) groups in their molecules. The thiol groups adsorb onto metal surfaces to form a dense protective film, while the carboxyl groups ensure water solubility, all resulting in highly effective corrosion inhibition. Quaternary ammonium salts are preferred for thermal stability in high-temperature environments (>150°C); amides are preferred for enhanced salt tolerance in highly salinized environments (>200,000 mg / L NaCl); and thioethers are preferred for improved corrosion inhibition efficiency in highly corrosive environments. Mercapto-carboxyimidazoline quaternary ammonium salts are preferred in this application. The quaternary ammonium cations in these salts impart excellent high-temperature stability (withstand temperatures above 150°C), making them suitable for deep, high-temperature oil reservoirs. They also offer a reasonable salt tolerance (withstands 50,000-100,000 mg / L NaCl), low toxicity, and stable corrosion inhibition efficiency, meeting the long-term protection needs of metal equipment in high-temperature oil reservoirs.
[0032] In a possible embodiment, the modified mesoporous silica nanoparticles are modified by amino modification using 3-aminopropyltriethoxysilane.
[0033] Specifically, 3-aminopropyltriethoxysilane (APTES) was used to modify the mesoporous silica nanoparticles by amino modification. The amino group (-NH2) in the APTES molecule can efficiently load anionic surfactants through electrostatic action, enhance interfacial activity and promote crude oil stripping; its ethoxysilane group reacts with the hydroxyl group on the surface of mesoporous silica after hydrolysis to form a stable Si-O-Si chemical bond, significantly improving the mechanical strength of the carrier and preventing particle breakage; the amino group enhances the hydrophilicity of the material, improves dispersion stability, and avoids agglomeration and precipitation.
[0034] The present application also provides a method for preparing a high-temperature and high-salt resistant nano-infiltrator, which is used to prepare a high-temperature and high-salt resistant nano-infiltrator, such as Figure 1 As shown, the following steps are included: Step 1: mixing nanocellulose and amino-modified mesoporous silica in deionized water, ultrasonically dispersing the mixture, and then spray drying the mixture; Step 2: adding rhamnolipid and anionic surfactant to a buffer solution with a pH of 7 and stirring until dissolved, then adding the product obtained in step 1, stirring at 50-60° C. for 2-3 hours, and simultaneously performing ultrasonic dispersion; Step 3, adding the product obtained in step 2 to deionized water dissolved with citrate-modified sodium zirconium phosphate, stirring at 50-60° C. for 1-2 hours, and performing solid-liquid separation to obtain a solid product; Step 4: adding polyethylene glycol-block-poly-ε-caprolactone, the mercapto-carboxy imidazoline derivative and the solid product obtained in step 3 into anhydrous ethanol and stirring and mixing to obtain a nano-permeating agent.
[0035] Specifically, step 1 involves pre-treating the nanocellulose and amino-modified mesoporous silica. The process involves adding the nanocellulose and amino-modified mesoporous silica in a proportional amount to deionized water, stirring thoroughly to form a uniform mixture, and then performing ultrasonic dispersion at a power level of 300-500W for approximately 30-60 minutes. The mixture is then dried using a spray dryer. Ultrasonic dispersion breaks up nanoparticle agglomerations, allowing the two materials to fully contact and evenly mix. Spray drying transforms the mixture into a fluffy, porous composite powder, increasing the loading capacity of subsequent active ingredients and enhancing the dispersion stability of the system.
[0036] Step 2 involves the loading and preliminary compounding of the surfactant. Specifically, the rhamnolipid and anionic surfactant are sequentially added to a pH 7 buffer solution. A magnetic stirrer is used at 300–500 rpm until completely dissolved. The composite powder prepared in step 1 is then added and stirred in a constant-temperature water bath at 50–60°C for 2–3 hours. Ultrasonic dispersion is performed during this period. Finally, the solvent is removed by vacuum drying or freeze-drying to obtain a composite powder loaded with the rhamnolipid and anionic surfactant. Ultrasonic stirring is used to promote uniform adsorption of the surfactant onto the composite carrier surface. Optimal temperature and pH ensure the activity of the surfactant and its stable binding to the carrier. The buffer is either phosphate or borate buffer.
[0037] Step 3 is the introduction of the salt-resistant component and solid-liquid separation: Dissolve sodium zirconium phosphate modified with citrate in deionized water to form a transparent solution. Add the composite powder loaded with rhamnolipid and anionic surfactant to this solution, and stir at a speed of 300 - 400 r / min in a constant temperature water bath at 50 - 60 °C for 1 - 2 h. After stirring, obtain the solid product by centrifugal separation or filtration, and wash it several times with deionized water and then dry it. The sodium zirconium phosphate modified with citrate effectively inhibits the salting-out phenomenon caused by high-valence cations through the electrostatic shielding effect of the citrate between layers, improving the salt resistance of the system. Stirring at low temperature ensures the stability of its crystal structure. After solid-liquid separation, composite particles with salt-resistant functions are obtained, enhancing the adaptability of the nano-infiltration agent in complex reservoir environments.
[0038] Step 4: Dissolve polyethylene glycol-block-poly(ε-caprolactone) (PEG-b-PCL) and mercapto-carboxyl imidazoline quaternary ammonium salt in anhydrous ethanol in proportion, add the solid product obtained after drying in Step 3, and disperse it by high-speed shearing at a speed of 10000 r / min for 10 min. Then, after filtering through a 0.22 μm filter membrane, a uniform and stable nano-infiltration agent emulsion is obtained.
[0039] The nano-infiltration agent in this application uses amino-functionalized mesoporous silica as a carrier to load surfactants, strengthens salt resistance through sodium zirconium phosphate modified with citrate, combines a PEG-b-PCL slow-release carrier and a mercaptoimidazoline derivative corrosion inhibitor to form a liquid system with efficient crude oil stripping, salt resistance and corrosion protection, and slow-release functions. Its nano-porous structure and microemulsion characteristics make the system have low viscosity and strong permeability, and still maintain an interfacial tension ≤ 0.1 mN / m in high-temperature and high-salt environments, improving the crude oil recovery rate. At the same time, the corrosion inhibition efficiency ≥ 85%. The preparation method of this application realizes the uniform coating of active components through a step-by-step loading and composite process, and uses ultrasonic-assisted dispersion and high-speed shearing techniques. The combination of spray drying and ethanol dispersion not only ensures the mechanical strength of the carrier but also forms a stable liquid system, and the process flow is simple and controllable.
[0040] In a possible implementation manner, in Step 1, the preparation process of the amino-functionalized mesoporous silica nanoparticles includes: Disperse the mesoporous silica nanoparticles in anhydrous toluene, add 3-aminopropyltriethoxysilane, and reflux and react at 60 - 80 °C for 4 - 6 h under nitrogen protection.
[0041] Specifically, during the preparation of amino-modified mesoporous silica nanoparticles, the mass ratio of mesoporous silica nanoparticles (MSN) to 3-aminopropyltriethoxysilane (APTES) was 1:1, and the amount of anhydrous toluene was 5 to 20 times the mass of MSN. The MSN was first dispersed in anhydrous toluene to form a uniform suspension. After the addition of APTES, the suspension was refluxed at 60 to 80°C under nitrogen for 4 to 6 hours. The ethoxysilane groups (-Si(OC2H5)3) in the APTES molecule undergo hydrolysis in anhydrous toluene solvent to generate silanol groups (-Si-OH). This process spontaneously produces a slightly acidic environment due to the weak polarity of the toluene solvent and the high temperature conditions. The generated silanol groups then undergo condensation reactions with the hydroxyl groups (-OH) on the MSN surface to form stable Si-O-Si covalent bonds. At the same time, the amino groups (-NH2) of APTES are firmly grafted to the MSN surface through chemical bonding. Nitrogen protection prevents APTES oxidation and avoids moisture interference with the hydrolysis reaction. The reflux temperature accelerates the reaction kinetics and promotes the uniform distribution of silanol groups, ultimately forming a high-density amino functional layer on the MSN surface, which not only enhances the hydrophilicity of the material but also provides active sites for subsequent loading, while maintaining the integrity of the mesoporous structure to ensure high specific surface area and pore volume characteristics.
[0042] In one possible embodiment, in step 1, the spray drying process includes: the inlet temperature is initially set to 140°C, and after running for 10-15 minutes, it is gradually lowered by 2-3°C each time until it reaches 130°C, and the entire process lasts for 45-60 minutes.
[0043] Specifically, the spray drying process adopts a gradient cooling strategy. The initial inlet temperature is set to 140°C to quickly evaporate the surface moisture of the material to form a hard shell to prevent adhesion. After running for 10 to 15 minutes, the temperature is gradually lowered by 2 to 3°C each time until it stabilizes at 130°C. The entire cooling process lasts for 45 to 60 minutes. Among them, the high temperature stage quickly forms a surface protective film to prevent particle agglomeration. The gradient cooling stage allows the internal moisture of the particles to slowly migrate to the surface and dynamically balance with the surface evaporation rate, preventing the rapid increase in internal vapor pressure due to rapid water loss and the destruction of the mesoporous structure, and avoiding the degradation of amino groups caused by long-term high temperature. The final composite powder has a uniform pore size distribution and a high amino retention rate, which significantly improves its storage stability and subsequent loading efficiency.
[0044] In a possible embodiment, the parameters of the ultrasonic treatment in step 2 include: a frequency of 40 to 60 kHz and a duration of 30 to 50 minutes.
[0045] Specifically, the ultrasonic treatment in step 2 is carried out at a frequency of 40 - 60 kHz for 30 - 50 min. The ultrasonic waves within this parameter range can effectively break the aggregation state among surfactant molecules, promote the full dissociation and uniform dispersion of rhamnolipid and anionic surfactant in the buffer solution. Meanwhile, through the cavitation effect, the adsorption ability of surfactant molecules on the surface of the composite carrier is enhanced, making the interfacial active layer more dense and stable. The appropriate duration ensures that surfactant molecules penetrate into the internal pores of the carrier, forming a synergistic wetting modification effect inside and outside, significantly improving the ability of the system to reduce the oil-water interfacial tension, enhancing the emulsification and dispersion efficiency of crude oil, and providing stronger interfacial activity for the subsequent oil displacement process.
[0046] The high-temperature and high-salt resistant nano-infiltration agent in this application is applied to oil exploitation and can be directly injected into underground oil layers. Firstly, by efficiently reducing the oil-water interfacial tension, the adsorption bondage between crude oil and the rock surface is released; secondly, relying on the sustained release of active ingredients by the slow-release carrier, deep profile control and displacement and crude oil stripping are achieved; thirdly, due to its excellent temperature and salt resistance performance, it can remain stable for a long time under the environment of 150 °C high temperature and 200,000 mg / L salinity, significantly improving the crude oil recovery rate, reducing the energy consumption of water injection development, and extending the production cycle of oil wells. It is particularly suitable for the efficient development of high-temperature and high-salt complex oil reservoirs such as the Bohai Bay and Tarim, providing key technical support for the stable production and increased production of old oil fields.
[0047] The present application is further illustrated by the following examples: Example 1 Disperse mesoporous silica nanoparticles in anhydrous toluene, add 3-aminopropyltriethoxysilane, and reflux at 70 °C for 4 - 6 h under nitrogen protection. Among them, the mass ratio of mesoporous silica nanoparticles, 3-aminopropyltriethoxysilane to anhydrous toluene is 1:1:15.
[0048] Example 2 Based on the total mass of each component, weigh 20% of amino-functionalized mesoporous silica nanoparticles, 4% of nanocellulose, 28% of rhamnolipid, 9% of sodium dodecylbenzenesulfonate, 6% of modified sodium zirconium phosphate, 9% of polyethylene glycol-b-polycaprolactone, and 2% of mercapto-carboxy imidazoline derivative by weight percentage.
[0049] Step 1: Mix nanocellulose and amino-functionalized mesoporous silica in deionized water, ultrasonically disperse for 45 min at a frequency of 400 W. The initial inlet temperature is set at 140 °C, and after running for 10 min, it starts to be gradually lowered by 2 °C each time until it reaches 130 °C. The whole process lasts for 45 min, and then spray drying is carried out.
[0050] Step 2: Add rhamnolipid and sodium dodecylbenzenesulfonate to a phosphate buffer solution with a pH of 7. After stirring and dissolving, add the composite powder prepared in Step 1, stir in a 50°C water bath for 3 h with ultrasonic assistance, and then perform vacuum drying.
[0051] Step 3: Add the composite powder loaded with rhamnolipid and sodium dodecylbenzenesulfonate obtained in Step 2 to citrate-modified sodium zirconium phosphate, stir at 50°C for 1 h, wash several times with deionized water, and then centrifuge and dry.
[0052] Step 4: Dissolve polyethylene glycol-b-polycaprolactone and mercapto-carboxyl imidazoline quaternary ammonium salt in absolute ethanol, add the product obtained in Step 3, perform high-speed shearing at a speed of 10000 r / min, and filter to obtain a nano-adsorbent emulsion.
[0053] Example 3 Based on the total mass of each component, weigh 20% of amino-functionalized mesoporous silica nanoparticles, 4% of nanocellulose, 28% of rhamnolipid, 9% of sodium dodecylbenzenesulfonate, 6% of modified sodium zirconium phosphate, 9% of polyethylene glycol-b-polycaprolactone, and 2% of mercapto-carboxyl imidazoline amide by weight percentage.
[0054] Step 1: Mix nanocellulose and amino-functionalized mesoporous silica in deionized water, perform ultrasonic dispersion at a frequency of 500 W for 50 min. Initially set the inlet temperature to 140°C, start gradually decreasing it after running for 10 min, decrease it by 3°C each time, and gradually decrease it to 130°C. The whole process lasts for 50 min, and then perform spray drying.
[0055] Step 2: Add rhamnolipid and petroleum sulfonate to a borate buffer solution with a pH of 7. After stirring and dissolving, add the composite powder prepared in Step 1, stir in a 55°C water bath for 2.5 h with ultrasonic assistance, and then perform vacuum drying.
[0056] Step 3: Add the composite powder loaded with rhamnolipid and petroleum sulfonate obtained in Step 2 to citrate-modified sodium zirconium phosphate, stir at 55°C for 1.5 h, wash several times with deionized water, and then centrifuge and dry.
[0057] Step 4: Dissolve polyethylene glycol-b-polycaprolactone and mercapto-carboxyl imidazoline quaternary ammonium salt in absolute ethanol, add the product obtained in Step 3, perform high-speed shearing at a speed of 10000 r / min, and filter to obtain a nano-adsorbent emulsion.
[0058] Example 4 Based on the total mass of each component, weigh 20% of amino-functionalized mesoporous silica nanoparticles, 4% of nanocellulose, 28% of rhamnolipid, 9% of sodium dodecylbenzenesulfonate, 6% of modified sodium zirconium phosphate, 9% of polyethylene glycol-b-polycaprolactone, and 2% of mercapto-carboxyl imidazoline sulfide by weight percentage.
[0059] Step 1: Mix nanocellulose and aminated mesoporous silica in deionized water, ultrasonically disperse for 50 min at a frequency of 600 W. Initially set the inlet temperature at 140 °C, start gradually decreasing it after running for 10 min, with each decrease of 3 °C, gradually decrease to 130 °C, and the whole process lasts for 60 min, then spray dry.
[0060] Step 2: Add rhamnolipid and petroleum sulfonate to a borate buffer solution with a pH of 7. After stirring and dissolving, add the composite powder prepared in Step 1, stir in a 60 °C water bath for 3 h with ultrasonic assistance, and then vacuum dry.
[0061] Step 3: Add the composite powder loaded with rhamnolipid and petroleum sulfonate obtained in Step 2 to sodium citrate-modified sodium zirconium phosphate, stir at 60 °C for 2 h, wash several times with deionized water and then centrifuge and dry.
[0062] Step 4: Dissolve polyethylene glycol-b-polycaprolactone and mercapto-carboxyl imidazoline thioether in absolute ethanol, add the product obtained in Step 3, perform high-speed shearing at a speed of 10,000 r / min, and filter to obtain a nano-adsorbent emulsion.
[0063] Performance detection: 1. Salt tolerance test Using a surface tensiometer (platinum ring method), test the interfacial tension of the nano-infiltration agent under high-temperature and high-salt conditions. The specific operation is as follows: First, prepare simulated formation water containing 200,000 mg / L NaCl, add 1 wt% nano-infiltration agent solution into it, and ultrasonically disperse for 10 minutes to ensure uniformity; then place the solution in a constant-temperature water bath at different temperatures (80 °C, 100 °C, 150 °C, 200 °C) for 1 hour, take it out and immediately measure the interfacial tension with a surface tensiometer, and repeat the test 3 times at each temperature and take the average value. By comparing the changes in interfacial tension at different temperatures and salinities, evaluate the stability of the infiltration agent in a high-temperature and high-salt environment. The test results are shown in Table 1.
[0064] Table 1 Interfacial tension of nano-infiltration agent
[0065] As can be seen from Table 1, the examples all show good interfacial stability under high-temperature and high-salt conditions. The interfacial tension increases slightly with the increase of temperature, but all remain below 0.1 mN / m. Among them, the interfacial tension of Example 2 is the lowest at 0.085 mN / m under the conditions of 200 °C and 200,000 mg / L NaCl, indicating that its comprehensive performance of temperature and salt tolerance is the best and it is suitable for the development of high-temperature and high-salt oil reservoirs.
[0066] 2. Self-infiltration performance test Using a capillary self - absorption device, inject the nano - imbibition agent solution into the core holder and let it stand under different temperatures (25°C, 80°C, 100°C, 150°C, 200°C). Measure the capillary self - absorption height at different time points (0.5 h, 1 h, 2 h, 4 h, 8 h, 12 h, 24 h) to evaluate the oil displacement efficiency of the imbibition agent. The test results are shown in Table 2.
[0067] Table 2 Self - absorption height of nano - imbibition agent
[0068] As shown in Table 2, each example shows excellent self - absorption performance at different temperatures, and the self - absorption height is greater than 20 cm. Among them, as the temperature increases, the decrease amplitude of the self - absorption height is the smallest, indicating that its imbibition oil displacement efficiency is the best, which can quickly drive the crude oil out of the rock pores and significantly improve the recovery efficiency.
[0069] 3. Imbibition recovery rate Vacuum the reservoir natural core to 0.08 MPa and saturate it with simulated formation water (salinity 200,000 mg / L NaCl). Let it stand at 60°C for 24 hours to ensure full wetting, and then place it in an 80°C constant - temperature oven to saturate it with degassed crude oil. After standing for 24 hours, measure the original oil content (determined by the weighing method). Take out the core, dry its surface, put it into a ground - glass graduated flask containing 10 mL of imbibition agent solution (corresponding to the formula of the example), and place it in a constant - temperature water bath at 80°C, 100°C, 150°C, 200°C respectively to stand. Record the imbibed oil volume every 0.5 hours, and calculate the recovery rate (%) after 24 hours. The results are shown in Table 3.
[0070] Table 3 Imbibition recovery rate of nano - imbibition agent
[0071] As can be seen from Table 3, each example shows excellent imbibition recovery rate. The recovery rate exceeds 60% at 80°C, and even when the temperature rises to 200°C, the recovery rate still remains above 48%. This indicates that the nano - imbibition agent has good temperature - resistance performance and oil displacement efficiency, and is suitable for the development of high - temperature and high - salinity oil reservoirs.
[0072] The above are only the preferred embodiments of the present invention and are not used to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A high temperature and high salt resistant nano-infiltrator, characterized in that: The invention comprises, by weight percentage, 15-25% modified mesoporous silica nanoparticles, 3-8% nanocellulose, 25-35% rhamnolipid, 8-12% anionic surfactant, 5-8% modified sodium zirconium phosphate, 8-12% polyethylene glycol-b-polycaprolactone and 1-5% mercapto-carboxy imidazoline derivative; Wherein, the modified mesoporous silica nanoparticles are amino-modified mesoporous silica nanoparticles; and the modified sodium zirconium phosphate is citrate-modified sodium zirconium phosphate.
2. The high-temperature and high-salt nano imbibition agent according to claim 1, wherein The anionic surfactant is sodium dodecylbenzenesulfonate or petroleum sulfonate.
3. The high-temperature and high-salt nano imbibition agent according to claim 1, wherein The particle size of the modified mesoporous silica nanoparticles before modification is 5-10 nm, and the specific surface area is ≥ 1000 m 2 / g.
4. The high-temperature and high-salt nano imbibition agent according to claim 1, characterized in that The mercapto-carboxyimidazoline derivative is one of mercapto-carboxyimidazoline quaternary ammonium salt, mercapto-carboxyimidazoline amide and mercapto-carboxyimidazoline sulfide.
5. The high-temperature and high-salt nano imbibition agent according to claim 1, wherein The modified mesoporous silica nanoparticles are modified by amino modification using 3-aminopropyltriethoxysilane.
6. Use of the high-temperature-resistant, high-salt nano-imbibition agent according to any one of claims 1 to 5 in oil production.
7. A preparation method of a high-temperature and high-salt resistant nano imbibition agent, characterized in that, The high temperature resistant and high salt nano-absorbing agent according to any one of claims 1 to 5 comprises the following steps: Step 1: mixing nanocellulose and amino-modified mesoporous silica in deionized water, ultrasonically dispersing the mixture, and then spray drying the mixture; Step 2: adding rhamnolipid and anionic surfactant to a buffer solution with a pH of 7 and stirring until dissolved, then adding the product obtained in step 1, stirring at 50-60° C. for 2-3 hours, performing ultrasonic dispersion, and then drying; Step 3, adding the product obtained in step 2 to deionized water dissolved with citrate-modified sodium zirconium phosphate, stirring at 50-60° C. for 1-2 hours, and performing solid-liquid separation to obtain a solid product; Step 4: adding polyethylene glycol-b-polycaprolactone, the mercapto-carboxyimidazoline derivative and the solid product obtained in step 3 into anhydrous ethanol and stirring and mixing to obtain a nano-permeating agent.
8. The preparation method of the high-temperature and high-salt nano imbibition agent according to claim 7, characterized in that, In step 1, the preparation process of the amino-modified mesoporous silica nanoparticles includes: Mesoporous silica nanoparticles were dispersed in anhydrous toluene, 3-aminopropyltriethoxysilane was added, and the mixture was refluxed at 60-80°C for 4-6 hours under nitrogen protection.
9. The preparation method of the high-temperature and high-salt nano imbibition agent according to claim 7, characterized in that, In step 1, the spray drying comprises: the inlet temperature is initially set to 140° C., and after running for 10 to 15 minutes, it is gradually lowered by 2 to 3° C. each time until it reaches 130° C. The entire process lasts for 45 to 60 minutes.
10. The preparation method of the high-temperature and high-salt nano imbibition agent according to claim 7, characterized in that, The parameters of the ultrasonic treatment in step 2 include: frequency 40-60 kHz, duration 30-50 min.
Citation Information
Patent Citations
Oily corrosion inhibitor and preparation method thereof
CN116554940A
Shale oil reservoir biological nano imbibition oil displacement agent and preparation method thereof
CN117625164A
Preparation method of high-temperature corrosion inhibitor
CN119372655A
Nano imbibition agent suitable for shale oil reservoir and preparation method of nano imbibition agent
CN119955500A
Imbibition oil displacement agent and preparation method therefor
WO2022252620A1
Cited By
Nanometer imbibition oil displacement blocking remover and preparation method thereof
CN120904871A
Photo-thermal enhanced composite oil sludge demulsifier and preparation method thereof
CN121063800A
High-salt-resistant corrosion inhibition type nano imbibition agent as well as preparation method and application thereof
CN121362574A
High-salt-resistant corrosion-inhibiting nano-impregnating agent, preparation method and application thereof
CN121362574B
Pavement composite soil stabilizer as well as preparation method and application thereof
CN121379611A